2019
DOI: 10.1002/smi.2871
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and neuroinflammatory biomarkers—The role of sex

Abstract: Despite the growing interest in adverse childhood experiences and biomarkers, less attention has been paid to multiple biomarkers as representing interrelated systems among college students. Guided by the neuroinflammatory pathway hypothesis, the current project takes the initial step in examining the link between three types of childhood adversity and biomarkers of neuroplasticity (brain-derived neurotropic factor [BDNF]) and low-grade inflammation (C-reactive protein [CRP]) in an overarching model and whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Findings revealed that ACEs were associated with dysfunctional activity in these biomarkers (Carroll et al, 2013; Drury et al, 2014; Fuller-Rowell et al, 2019). Specifically, experiencing more ACEs was associated with reductions in cortisol reactivity (Peckins et al, 2012), BDNF (S. Kim et al, 2019), and SICAM-1 (Slopen et al, 2010) as well as a resistance to insulin in diabetic participants (Fuller-Rowell et al, 2019). ACEs were also associated with increased levels of inflammatory markers including CRP ( n Total = 7; n Significant = 4), E-selectin ( n Total = 2; n Significant = 2), IL-6 ( n Total = 2; n Significant = 2), CTNFα ( n Total = 1; n Significant = 1), and fibrinogen ( n Total = 1; n Significant = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Findings revealed that ACEs were associated with dysfunctional activity in these biomarkers (Carroll et al, 2013; Drury et al, 2014; Fuller-Rowell et al, 2019). Specifically, experiencing more ACEs was associated with reductions in cortisol reactivity (Peckins et al, 2012), BDNF (S. Kim et al, 2019), and SICAM-1 (Slopen et al, 2010) as well as a resistance to insulin in diabetic participants (Fuller-Rowell et al, 2019). ACEs were also associated with increased levels of inflammatory markers including CRP ( n Total = 7; n Significant = 4), E-selectin ( n Total = 2; n Significant = 2), IL-6 ( n Total = 2; n Significant = 2), CTNFα ( n Total = 1; n Significant = 1), and fibrinogen ( n Total = 1; n Significant = 1).…”
Section: Resultsmentioning
confidence: 99%
“…This may be partially attributable to the relatively few studies that specifically examined BDNF protein levels, the relatively small sample sizes within these studies, and the variation in study design that our own meta-analysis also encountered. Despite a strong rationale for the involvement of BDNF in mental health disorders, the possible link between ACE exposure and BDNF activity remains unclear, particularly in comparison to HPA biomarkers ( e.g ., cortisol) and inflammatory biomarkers (Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A member of the neurotrophin family of growth factor proteins, BDNF binds to Tropomyosin receptor kinase B (TrkB) receptors on neurons of the central and peripheral nervous systems where it supports neuronal survival and encourages neurogenesis (Binder & Scharfman, 2004). BDNF has predominantly been treated as a biomarker of synaptic plasticity (Benedetti et al, 2017; Kim, Watt, Ceballos, & Sharma, 2019), and due to its secretion by activated lymphocytes and the ability of IL-6 and TNF-α to augment BDNF release from the nervous system (Jin, Sun, Yang, Cui, & Xu, 2019; Kraneveld et al, 2014), BDNF activity resides at the intersection of neural development, memory formation, and neuroimmunology (Bekinschtein, Cammarota, Izquierdo, & Medina, 2007; Calabrese et al, 2014; Kim et al, 2019). In addition to BDNF’s modulation of the immune axis, it has also been implicated in instigating dysregulation of the HPA axis, with elevated BDNF levels contributing to hyperactivity of the HPA axis – a common molecular change seen in ACE-exposed children (K. S. Dempster et al, 2021; Naert, Ixart, Maurice, Tapia-Arancibia, & Givalois, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent evidence linked compromised neural development and neuroinflammatory reactions to ACEs. [72][73][74] The compromised growth and development processes, in turn, could hinder socioeconomic attainment in adulthood which undermines health.…”
Section: Discussionmentioning
confidence: 99%